2022
DOI: 10.12998/wjcc.v10.i5.1716
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab-associated diffuse interstitial lung disease in patients with ulcerative colitis: A case report

Abstract: BACKGROUND Vedolizumab, a newer class of integrin antagonist biological agents, has been applied to treat patients with moderate-to-severe Crohn’s disease (CD) and ulcerative colitis (UC), especially for patients who are refractory to traditional therapies and tumor necrosis factor antagonists. However, some rare but life-threatening adverse effects warrant pharmacovigilance. We describe the first fatal case of vedolizumab-associated severe diffuse interstitial lung disease in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The purpose of our case report is to show the possibility that Vedolizuamb causes pulmonary hemorrhage such as many other monoclonal antibodies to different farmodynamics like Infliximab, Ustekinumab and others [9,18,20]. In fact, rapid onset pulmonary manifestations are known, which if caught in time can be managed safely for the patient [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of our case report is to show the possibility that Vedolizuamb causes pulmonary hemorrhage such as many other monoclonal antibodies to different farmodynamics like Infliximab, Ustekinumab and others [9,18,20]. In fact, rapid onset pulmonary manifestations are known, which if caught in time can be managed safely for the patient [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated its efficacy in treating IBD; for instance, an analysis of homing receptor expression on T cells in peripheral blood and inflamed mucosa showed that treatment with vedolizumab is associated with a significant expansion of regulatory T cells in peripheral blood without a significant increase in viral infections in the IBD group ( 33 ). Therefore, as the only gut-selective biologic that specifically targets the α4β7 gastrointestinal integrin receptor, vedolizumab represents a promising therapeutic option for IBD ( 34 ). Ustekinumab, a human IgG antibody targeting the p40 subunit common to both IL-12 and IL-23, operates differently from anti-TNF therapies ( 35 ).…”
Section: Treatment Methods For Ibdmentioning
confidence: 99%
“…By withholding vedolizumab and giving steroid therapy, the patient was successfully treated [156]. Recently, other case reports documented the possibility of vedolizumab-induced lung injury [157][158][159].…”
Section: Vedolizumabmentioning
confidence: 99%